Analysis of Factors Affecting Decision Making in MSMEs Case Study: Buronan Ndower - Putri Sahya Fadiah; Kurnianingsih, Fera; Sagita, Safa Alifiah; Hidayat N, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2025)
Payment methods have a significant impact today due to various factors related to technological developments, changes in consumer behavior, and market dynamics. One of the latest innovations in payment methods widely established in Indonesia is using the QR Code Indonesian Standard (QRIS). The use of QRIS continues to increase along with the development of digital technology and changes in consumer behavior, which prefers easier transactions. This qualitative research uses a questionnaire survey containing questions relevant to the research objectives. Based on the research results, the QRIS payment method is one of the factors influencing buyer decisions, focusing on three main indicators: ease of use, transaction speed, and transaction security. The positive effect of the QRIS payment method contributes to increasing customer satisfaction, making consumers feel comfortable and safe and having a good shopping experience, so they tend to make purchases and choose QRIS as a payment method.